Cosmetic Product Usage and Self-Esteem Among Psychology Students of Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In today's generation, most people, especially women, are users of cosmetic products; someare using cosmetic products to boost their confidence, while others use cosmetic products forother personal reasons. Cosmetic product usage is the practice of maintaining and enhancingone’s physical appearance with various cosmetic products, including creams, lotions, andothers; these products are easily accessible to users here in the Philippines through variousdistributors. This study aimed to determine the significant relationship between cosmeticproduct usage and self-esteem among Psychology Students of Bestlink College of thePhilippines.The results found that the frequency of using cosmetic products and reasons for using themhave a very strong correlation, having a Pearson R-value of 0.9182. It also supports the claimsof Aquino J., Balanyos L., Botardo M., Mandanas K., Monte L., and Ordas E. (2017) thatpersonal reasons for choosing what cosmetics to wear lie in their own decision.Women can wear cosmetics to gain self-esteem; however, choosing when and why will dictatethat and give self-esteem to the users. This revealed that there are reasons that driverespondents to use cosmetic products that affect their self-esteem, such as when they wearcosmetics, they feel more confident to interact with others, and regularly, when usingcosmetics, boosts their self-assurance in social circumstances. It demonstrates that cosmeticproducts can increase self-esteem when used, considering why it was used because itdepends on their own decision and can be dictated by other factors. Ultimately, this study canhelp minority students gain self-esteem by using cosmetic products appropriate for their age,sex, and any other reasons.
Keywords: Mental Health